Budimpešta, mesto kot nalašč za razvoj kreativne industrije? - Egedy, Tamás (Urbani izziv, 2010)
The triggering factors of urban development have changed continuously over thepast decades, always adapting themselves to the processes of globalisation and related trends. Nowadays creativity, knowledge and innovation are broadly recognised as the essential ingredients of economic success in the advanced capitalist world. Thus, creative and knowledge-intensive industries are increasingly seen as the most important economic activities for international competitiveness. In terms of metropolitan regions, eastern European cities have a special position because of their belated entrance into and development in the creative economy. The current trends taking place within the creative economies of metropolitan regions in eastern Europe could also influence the future economic perspectives of the European Union. Regarding the new economic development tendencies outlined above, this paper highlights the capacity and potentials of the Budapest Metropolitan Region based on statistical analyses and results of empirical surveys and in-depth interviews carried out among creative professionals.
Keywords: Budapest; Budimpešta; industrija; industrijska podjetja; inovativnost; knowledge; lokacija; uspešnost; znanje